Pengaruh Kualitas Pelayanan, Kualitas Produk, Nilai Pelanggan, dan Bagi Hasil terhadap Kepuasan Anggota: Studi pada Koperasi Syariah Binama Weleri - Firdaus, Muhamad Zidan Miftah; Achyani, Fatchan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of service quality, product quality, customer value and profit sharing on member satisfaction at Binama Islamic Cooperative, weleri branch. This type of research is quantitative. The data source is obtained by questionnaire. The population in this study were all members of the Binama Islamic Cooperative, weleri branch. The sampling technique used purposive sampling with certain criteria so that 109 respondents were obtained as a research sample. The data analysis technique uses Multiple Linear Regression Analysis using SPSS 25 software. The results of the study state that service quality, product quality, customer value and profit sharing have an influence on member satisfaction at the weleri branch of Binama Islamic Cooperative. Keywords: Service Quality, Product Quality, Customer Value, Profit Sharing, Member Satisfaction